PENGARUH KEPATUHAN DAN PENGAWASAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI EMPIRIS PADA PEMERINTAH KABUPATEN MINAHASA UTARA) - Mawuntu, Nikita Srisilia; Manossoh, Hendrik; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Local Government Financial Statement is an information media for the society that gives information about the financial position and the performance of local government. Therefore, a financial statement should be qualified, reliable, accountable and transparent to meet the public requirement. Some factors are considered capable to improve the quality of Local Government Financial Statement. They are compliance with the rule of law and internal control. This study aims to obtain empirical evidence of the influence of compliance to the rule of law and internal control toward the quality of Minahasa Utara Regency Government Financial Statement. There are 60 respondents as the samples have been taken from 24 Local Government Organization used in this research. It uses quantitative analysis method and questionnaire instrument as primary data collection and process the data by SPSS version 23. The statistic method that used to verify the hypothesis is by multiple linear regression analysis. The hypothesis test results show that compliance to the rule of law has a positive and significant effect to the quality of Local Government Financial Statement while internal control has no significant and positive influence to the Financial Statement of Minahasa Utara Regency Government.